2009
DOI: 10.1103/physrevb.80.115113
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of radiation loss by hybridization effect in two coupled split-ring resonators

Abstract: This paper investigates the radiation properties of two coupled split-ring resonators (SRRs). Due to electromagnetic coupling, two hybrid magnetic plasmon modes were induced in the structure. Our calculations show that the radiation loss of the structure was greatly suppressed by the hybridization effect. This led to a remarkable increase in the Q-factor of the coupled system compared to the single SRR. By adjusting the distance between the two SRRs, the Q-factor changed correspondingly due to different electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…It needs to specially point out that although the magnetic dipole has radiation losses, the radiation losses of the magnetic dipole are much lower than those of the corresponding electric dipole, which is consistent with the view proposed by Ref. [34]. As a result, the magnetic dipole (SRR) with the uniformly distributed current is expected to exhibit the low loss property.…”
Section: Zoomed In Viewsupporting
confidence: 64%
See 1 more Smart Citation
“…It needs to specially point out that although the magnetic dipole has radiation losses, the radiation losses of the magnetic dipole are much lower than those of the corresponding electric dipole, which is consistent with the view proposed by Ref. [34]. As a result, the magnetic dipole (SRR) with the uniformly distributed current is expected to exhibit the low loss property.…”
Section: Zoomed In Viewsupporting
confidence: 64%
“…However, it may not always be possible to find a suitable material to provide the necessary gain at a desired frequency regime. So far, the electromagnetically induced transparency (EIT) effects have been introduced to the metamaterial designs for suppressing the radiation losses [27][28][29][30][31][32][33][34][35][36]. Although the losses of the EIT-like metamaterials are very low, they do not maintain the negativity in the real part of constitutive parameters [27,29,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, especially when the elements are very close, this coupling effect is not negligible and will have a substantial effect on the properties of the metamaterials. Recent studies have shown that the resonance coupling effect between split-ring resonators (SRR) can introduce magnetoinductive waves [10][11][12][13][14][15][16], electroinductive waves [17,18], planar transmission lines [19], stereometamaterials [20][21][22] and radiation suppression [23]. Besides SRRs, the near-field coupling between other structures, such as nano-rods [24], fish-net [25] and nanosanwiches [26] are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining the material parameters of metamaterial structures is a well established procedure for isotropic, achiral media 17 . The approach has been extended for the cases of chiral, bianisotropic and inhomogeneous media [18][19][20][21] . An alternative approach based on the state-transition matrices has also been proposed for isotropic chiral media 22 , however none of these methods can be employed for the case of the C 4 symmetry group.…”
Section: Introductionmentioning
confidence: 99%